Combinations of scalp acupuncture location for the treatment of post-stroke hemiparesis: A systematic review and Apriori algorithm-based association rule analysis - Wang, Yu-Fang; Chen, Wei-Yi; Lee, Chang-Ti; Shen, Yi-Ying; Lan, Chou-Chin; Liu, Guan-Ting; Kuo, Chan-Yen; Chen, Mao-Liang; Hsieh, Po-Chun (Frontiers in Neuroscience, 2022)
Background: Post-stroke hemiparesis strongly affects stroke patients' activities of daily living and health-related quality of life. Scalp acupuncture (SA) is reportedly beneficial for post-stroke hemiparesis. However, there is still no standard of SA for the treatment of post-stroke hemiparesis. Apriori-algorithm-based association rule analysis is a kind of "if-then" rule-based machine learning method suitable for investigating the underlying rules of acupuncture point/location selections. This study aimed to investigate the core SA combinations for the treatment of post-stroke hemiparesis by using a systematic review and Apriori algorithm-based association rule analysis. Methods: We conducted a systematic review to include relevant RCT studies investigating the effects of SA treatment in treating patients with post-stroke hemiparesis, assessed by the Fugl-Meyer Assessment score. We excluded studies using herbal medicine or manual acupuncture. Results: We extracted 33 SA locations from the 35 included RCT studies. The following SA styles were noted: International Standard Scalp Acupuncture (ISSA), WHO Standard Acupuncture Point Locations (SAPL), Zhu's style SA, Jiao's style SA, and Lin's style SA. Sixty-one association rules were investigated based on integrated SA location data. Conclusions: SAPL_GV20 (Baihui), SAPL_GV24 (Shenting), ISSA_MS6_i (ISSA Anterior Oblique Line of Vertex-Temporal, lesion-ipsilateral), ISSA_MS7_i (ISSA Anterior Oblique Line of Vertex-Temporal, lesion-ipsilateral), ISSA_PR (ISSA Parietal region, comprised of ISSA_MS5, ISSA_MS6, ISSA_MS7, ISSA_MS8, and ISSA_MS9), and SAPL_Ex.HN3 (Yintang) can be considered the core SA location combination for the treatment of post-stroke hemiparesis. We recommend a core SA combination for further animal studies, clinical trials, and treatment strategies.